Obraz ciała a przekonanie o własnej skuteczności u sportowców i aktorów teatralnych = Body image and self-efficacy in sportsmen and theatre actors - Kolańska, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Body image is an important element of human self-assessment, which may affect the actions taken by him. Awareness of functioning and image their own body seems to play a significant role for the people doing the work, among other things as a sportsman, television presenter and actor. Sportsmen treat their bodies more in a category work tools with which to achieve sports results, which is their main target. The actors use their body as a of communication, emotions, desires on the stage.
Keywords: obraz ciała; przekonanie o własnej skuteczności; sport; aktor; body image; self-efficacy; actor